2006
DOI: 10.1111/j.1365-2796.2006.01691.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive‐behavioural stress management does not improve biological cardiovascular risk indicators in women with ischaemic heart disease: a randomized‐controlled trial

Abstract: Abstract. Claesson M, Birgander LS, Jansson J-H, Lindahl B, Burell G, Asplund K, Mattsson C (Umeå University Hospital, Umeå; Skellefteå Hospital, Skellefteå; and University of Uppsala, Uppsala; Sweden). Cognitive-behavioural stress management does not improve biological cardiovascular risk indicators in women with ischaemic heart disease: a randomized-controlled trial. J Intern Med 2006; 260: 320-331.Objectives. Psychosocial factors, such as stress and vital exhaustion, are associated with an increased risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 48 publications
1
20
0
1
Order By: Relevance
“…119 In contrast, cognitive behavioral stress management had no effect on several hemostasis measures in CHD patients when compared with usual care after 1 year. 121 The systematic provocation of laughter might also benefit low-grade hypercoagulability. 122…”
Section: Results From Intervention Studiesmentioning
confidence: 99%
“…119 In contrast, cognitive behavioral stress management had no effect on several hemostasis measures in CHD patients when compared with usual care after 1 year. 121 The systematic provocation of laughter might also benefit low-grade hypercoagulability. 122…”
Section: Results From Intervention Studiesmentioning
confidence: 99%
“…This homework can entail practicing problem-solving techniques, keeping a diary, practicing relaxation or participating in physical activities. Each group meeting has a specific subject, derived from the 6 components in the intervention [24]. These components concern 1) basic knowledge about cancer, treatment, healthy living and stress reactions, 2) self-awareness with the help of a diary for thoughts, feelings and behavior, as well as group discussions of specific cases 3) instruction in various techniques about how to express negative feelings, how to communicate with others more effectively how to change behaviors related to stress, anger, worry and depression 4) training these techniques in real-life situations outside the group, 5) cognitive restructuring with the help of diaries, techniques and group dynamics and 6) spirituality, in a broad sense, with group discussions of quality of life, values, self-confidence and optimism.…”
Section: Methodsmentioning
confidence: 99%
“…A 10-week CBSM intervention improved lymphocyte proliferative responses at the three-month follow-up in women with early-stage breast cancer (McGregor et al, 2004) and favorably changed the distribution of CD4 (helper T cells) and CD8 (suppressor or cytotoxic T cells) lymphocyte subsets in men with HIV (Antoni, 2003). However, other investigators found no significant changes in other physiologic responses (e.g., C-reactive protein) to CBSM in women with ischemic heart disease (Claesson et al, 2006;Claesson et al, 2005).…”
Section: Stress Management Adherence and Immune Responsesmentioning
confidence: 97%
“…A number of stress management programs have been implemented in various populations, but their impacts on immune responses have not been uniform. For example, cognitive-behavior stress management (CBSM) is one of the most widely used programs (Antoni, 2003;Antoni et al, 2001;Claesson et al, 2006;Claesson et al, 2005;Cruess et al, 2000;McGregor et al, 2004). A 10-week CBSM intervention improved lymphocyte proliferative responses at the three-month follow-up in women with early-stage breast cancer (McGregor et al, 2004) and favorably changed the distribution of CD4 (helper T cells) and CD8 (suppressor or cytotoxic T cells) lymphocyte subsets in men with HIV (Antoni, 2003).…”
Section: Stress Management Adherence and Immune Responsesmentioning
confidence: 99%